Learning from 360-degree videos on a VR headset compared to 2D videos on a monitor - Kulke, Louisa; Pasqualette, Laura (Cogent Education, 2024)
Online teaching has drastically increased over recent years. Although presentation of teaching videos in 360-degree on Virtual Reality headsets was shown to be more immersive than 2D videos, it is under debate whether people learn better from immersive 360-degree videos or 2D videos. The current preregistered study aimed to compare students’ learning success about a practical laboratory training in Electroencephalography from 360-degree videos shown on a VR headset compared to 2D videos. Forty-six participants responded to questions about Electroencephalography before and after watching a training video in 2D on a screen or in 360-degree on a VR headset. Their test score significantly improved and immediate learning performance was comparable in both conditions. However, participants preferred watching the 360-degree immersive videos on a VR headset and found them more practical. This suggests that both video formats can successfully be used in teaching contexts, though motivation to watch the video may be higher for 360-degree videos.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 2D videos; 360-degree videos; digital learning; Educational Psychology; immersive learning environment; learning; Psychological Science; Stephen Darwin; Universidad Alberto Hurtado; Chile; Technology